1967
DOI: 10.1128/jb.94.4.884-888.1967
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Division of Protoplasts of Bacillus megaterium and Inhibition of Division by Penicillin

Abstract: Protoplasts of Bacillus megaterium grew well and divided in nutrient broth containing 0.5 M NaCl as the stabilizer. Protoplasts also grew when sucrose or succinate was used instead of NaCl; however, no division phenomena were observed. The sequence of growth and division was similar to the results obtained by McQuillen. Protoplasts enlarged from 1.8 to 3.5 ,u in diameter, and then a small protuberance formed in the enlarged cells. The nodules enlarged until eventually symmetrical dumbbell-shaped bodies were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

1971
1971
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…However, balanced growth has not been unequivocally established for cultures of osmotically fragile cells. On the contrary, many earlier investigations of macromolecular biosynthesis in "protoplast" cultures demonstrated unbalanced (3,5,11) linear, rather than exponential, growth (6), or a lag prior to the onset of growth (5,9). A previous study from this laboratory indicated that "protoplasts" of Streptococcusfaecalik (ATCC 9790) could be obtained by treatment with lysozyme in the presence of 0.5 M sucrose (8).…”
mentioning
confidence: 85%
“…However, balanced growth has not been unequivocally established for cultures of osmotically fragile cells. On the contrary, many earlier investigations of macromolecular biosynthesis in "protoplast" cultures demonstrated unbalanced (3,5,11) linear, rather than exponential, growth (6), or a lag prior to the onset of growth (5,9). A previous study from this laboratory indicated that "protoplasts" of Streptococcusfaecalik (ATCC 9790) could be obtained by treatment with lysozyme in the presence of 0.5 M sucrose (8).…”
mentioning
confidence: 85%
“…Organism and cultivation . Candida albicans IFO (0600) was maintained on Sabouraud's glucose (SG) agar slants and successively subcultured twice at 30 various stabilizers (MgSO4, CaCl2, MnSO4, KC1, MgCl2, NaC1 or sucrose) at various concentrations. The plates were incubated at 30 C for 7 hr (preincubation) and then washed twice with water for 15 min each by pouring sterilized water onto the agar layer.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies on those osmolabile spherical bodies had thrown much light on the mechanism of their regeneration [10,12,13,16,18,24,26,38,41,42,47,60] and on cellular physiology. On the other hand, studies on the lysis of cell wall structures by these lytic enzymes had provided information on cell wall structures of bacteria and fungi, the mode of action of lytic enzymes and the mechanism of action of antibacterial and antifungal antibiotics [4,11,29,30,31,34,36,39,48,51].…”
mentioning
confidence: 99%
“…Bacillus subtilis NCIB 8054, ATCC 6633 was used throughout this study. Protoplasts were induced with the method devised for Bacillus megaterium by Kusaka (1967). During induction, lysozyme (EC 3.2.1.17, Sigma, UK) was used at a final concentration of 2040 units/ml and conversion into spherical protoplasts was monitored with phase and interference contrast microscopy (Reichert-Jung Polyvar Microscope, Austria).…”
Section: Organism and Protoplast Inductlonmentioning
confidence: 99%